Efficacy of resuscitative endovascular balloon occlusion of the aorta for hemorrhage control in patients with abnormally invasive placenta: a historical cohort study - Yuanhua Ye; Jing Li; Shiguo Liu; Yang Zhao; Yanhua Wang; Yijing Chu; Wei Peng; Caixia Lu; Chong Liu; Jun Zhou (BMC, 2023)
Abstract Background Patients with abnormally invasive placenta (AIP) are at high risk of massive postpartum hemorrhage. Resuscitative endovascular balloon occlusion of the aorta (REBOA), as an adjunct therapeutic strategy for hemostasis, offers the obstetrician an alternative for treating patients with AIP. This study aimed to evaluate the role of REBOA in hemorrhage control in patients with AIP. Methods This was a historical cohort study with prospectively collected data between January 2014 to July 2021 at a single tertiary center. According to delivery management, 364 singleton pregnant AIP patients desiring uterus preservation were separated into two groups. The study group (balloon group, n = 278) underwent REBOA during cesarean section, whereas the reference group (n = 86) did not undergo REBOA. Surgical details and maternal outcomes were collected. The primary outcome was estimated blood loss and the rate of uterine preservation. Results A total of 278 (76.4%) participants experienced REBOA during cesarean section. The patients in the balloon group had a smaller blood loss during cesarean Sect. (1370.5 [752.0] ml vs. 3536.8 [1383.2] ml; P < .001) and had their uterus salvaged more often (264 [95.0%] vs. 23 [26.7%]; P < .001). These patients were also less likely to be admitted to the intensive care unit after delivery (168 [60.4%] vs. 67 [77.9%]; P = .003) and had a shorter operating time (96.3 [37.6] min vs. 160.6 [45.5] min; P < .001). The rate of neonatal intensive care unit admission (176 [63.3%] vs. 52 [60.4%]; P = .70) and total maternal medical costs ($4925.4 [1740.7] vs. $5083.2 [1705.1]; P = .13) did not differ between the two groups. Conclusions As a robust hemorrhage-control technique, REBOA can reduce intraoperative hemorrhage in patients with AIP. The next step is identifying associated risk factors and defining REBOA inclusion criteria to identify the subgroups of AIP patients who may benefit more.